The effect of using a QR code-enhanced brochure on students’ knowledge and skill learning outcomes - Al-Sababha, Khairi Mahmoud H (Edelweiss Applied Science and Technology, 2024)
The objective of this study was to design a booklet supported by QR codes and assess its impact on cognitive achievement and the acquisition of gymnastics skills (front ball roll, ball back roll, and handstand). Technological applications play a crucial role in enhancing the teaching and learning experience. The study was conducted on 30 students from the College of Physical and Sports Sciences at the Hashemite University in Jordan. The participants were randomly divided into an experimental group and a control group, with 15 students in each group. The results of the study revealed that the experimental group, which utilized the QR Code-supported booklet, exhibited significantly higher scores and greater improvements compared to the control group. The experimental group demonstrated higher average scores in cognitive achievement and specific gymnastics skills, including forward roll, back roll, and handstand. The differences in improvement rates between the experimental and control groups were also notable. In this study, the intervention of the booklet with QR codes clearly improved the learning outcomes for the experimental group in terms of cognitive achievement and the learning of gymnastics skills (P < 0.05). Overall, this study highlights the positive impact of integrating QR codes into educational materials and processes. It suggests that the use of QR codes can be a valuable technological tool for improving learning outcomes and fostering student engagement. Furthermore, the study provides insights into future trends and possibilities for utilizing QR codes in educational settings.